(3GdebJaj dJGQjN CHj TGeIs - (3GdbGSe Hf eMeO Hf jhSa Hf eMeO Hf CHj jOGS, Yde GdOjf GdHQRGdj , CHh eMeO,J (B739 (3g` s; (3CHh TGeI GdebOSj , YHO GdQMef Hf ESeGYjd Hf EHQGgje GdebOSj GdOeTbj, TgGH GdOjf CHh GdbGSe,J (B665 (3g` s
(3ChdgG (B:s
(3ef SfI (B699 s
(3BNQgG (B:s
(3Edi SfI (B720 s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B125s
Keywords: (3GdJGQjNs